Integrating Smart Monitoring Systems in Urban Drug Abuse Prevention: A Case Study in Jakarta - Ismail, Ismail; Felecia, Felecia; Azizah, Anisa Kurniatul; Rahmawati, Diana (West Science Social and Humanities Studies, 2025)
Drug abuse remains a severe issue in urbanized cities, particularly in Jakarta, where illegal drug trafficking is common despite preventive actions. With this study, the implementation of a Smart Monitoring System (SMS) as an innovative technology to enhance drug abuse prevention is investigated. As a qualitative study, five key informants from law enforcement, policymakers, public health professionals, technologists, and community leaders were interviewed. The findings identify three major benefits of SMS: real-time tracking, improved integration of information, and increased public participation. However, several challenges such as privacy concerns, technological limitations, and resistance from stakeholders need to be addressed to enable an effective rollout. The study recommends the establishment of clear legislative regulations, infrastructure investment, public education campaigns, and inter-agency cooperation for the optimal utilization of SMS in Jakarta. These findings contribute to the technology-based crime prevention literature and provide pragmatic policy lessons for urban drug control policy.